Ответы и объяснения

2014-01-14T11:32:10+00:00
1. ...= (a + 3b) ( a^{2} - 3ab + 9 b^{2})
2. ...= (mn - k)( m^{2} n^{2}  + mnk + k^{2})
3. ...= ( x^{2} +  y^{2})( x^{4} - x^{2}y^{2} + y^{2})
4. ...= (k^{2}  - (pq)^{2})( k^{4} +  k^{2}  p^{2}  q^{2} +  p^{4}  q^{4})
5. ...= (a - b + b)( (a-b)^{2} - b(a-b) +  b^{2}) = a(a^{2}+2ab+b^{2} -ab + b^{2} + b^{2})a(a^{2} + ab + 3b^{2} )
6. ...=(x-2-3)((x-2)^{2} + 3(x-2) + 9) = (x - 5)(x^{2} - 4x + 4 + 3x - 6 + 9) = (x-5)(x^{2} - x + 7)
7. ...=(2a + a - b)( 4a^{2} - 2a(a - b) + (a-b)^{2}) = (3a - b)(4a^{2} - 2a^{2} + 2ab +  a^{2}  - 2ab +  b^{2} ) = (3a - b)(3a^{2} +  b^{2} )
8. ...= (3x - y(x - y))(9x^2 + 3xy(x-y) + y^2(x-y)^2) = (3x - xy - y^2)(9x^2+3x^2y - 3xy^2 + y^2(x^2-2xy+y^2)) = (3x - xy - y^2)(9x^2+3x^2y - 3xy^2 + y^2x^2 - 2xy^3 + y^4)